The Influence of Reuven Feuerstein's Application of the Theory of the Experience of Learning on the Strengthening of the Reading and Writing of Sixth Grade Students (Docentes 2.0 Journal, 2020)
The influence of the Theory called “Reuven Feuerstein's Mediated Learning Experience” modifies the nature of the interaction whose purpose is to strengthen the literacy of sixth-grade students at the El Tropezón Rural Education Center in the municipality of La Esperanza, located in the North of Santander. This study was carried out through Action Research with a mixed approach, for this, initially, a diagnostic evaluation was applied in order to establish the students' prior knowledge of the area of ??literacy, finding deficiencies in different proposed achievement indicators by the Ministry of National Education, for which a pedagogical proposal is designed integrating the theoretical foundations, the cognitive functions and the mental operations in the reading and writing competence through the methodology of the entrance, elaboration and exit phases, proposed in this theory . This proposal allowed the medication in the teaching-learning process of 20 students, carried out in two months with a distance modality due to the mandatory confinement by the COVID19, period which evidenced the consolidation of the literary-writer where it was observed that 80% of the students they had an improvement in the selected achievement indicators.
Keywords: Mediated Learning Experience; mediation; pedagogical proposal